Use of 18F-fluorodeoxyglucose positron emission tomography in the diagnosis of polymyalgia rheumatica—A prospective study of 99 patients. (7th October 2017) - Henckaerts, Liesbet; Gheysens, Olivier; Vanderschueren, Steven; Goffin, Karolien; Blockmans, Daniel
Abstract: Objective: Previous studies have shown that the majority of patients with PMR have increased 18 F-fluorodeoxyglucose (FDG) uptake around the shoulders, hips and processes of the cervical and lumbar spine on PET. The specificity of these findings for PMR is, however, not known. Methods: We prospectively included 99 consecutive patients with a possible clinical diagnosis of PMR. All patients underwent 18 F-FDG-PET scanning before treatment with glucocorticoids was started. The clinical suspicion of PMR was quantified by the treating physician on a scale from 1 to 5. FDG uptake was scored visually in 12 articular regions (scores 0–2) and a total skeletal score was calculated reflecting the FDG uptake in these 12 articular regions. Receiver operating characteristics analysis was performed to determine the optimal clinical and total skeletal score for diagnosing PMR. The gold standard for a diagnosis of PMR was the judgement of an experienced clinician after at least 6 months of follow-up. Results: Sixty-seven patients were diagnosed with PMR while 32 patients got another diagnosis. A clinical score of 4 or more had a sensitivity of 67.2%, specificity of 87.5%, positive predictive value (PPV) of 91.8% and a negative predictive value (NPV) of 56.0% for the diagnosis of PMR. A total skeletal score of 16 or more had a sensitivity, specificity, PPV and NPV of, respectively, 85.1, 87.5, 93.4 and 73.7%. Conclusion: 18 F-FDG-PET before starting glucocorticoid therapy improves the diagnostic accuracy compared with a clinical scoring system in patients with clinical suspicion of PMR.